Legal Review of Regulations Regarding Online Begging on Social Media Based on the Siyasah Fiqh Perspective - Simanungkalit, Diva Aulia; Pasaribu, Ilhamsyah (Law Development Journal, 2023)
This research aims to understand how online beggars develop on social media, find out how fiqh siyasa views online beggars on social media based on legal reviews in dealing with social problems. The method applied in this compilation is a normative-empirical approach which has descriptive-analytical characteristics, that is, it uses a method related to applying normative legal provisions (laws) to every event that occurs in society. Then an analysis of the data obtained is carried out systematically to obtain answers. Based on the research results, the government implements policies aimed at preventing and dealing with online beggars by issuing legal regulations. These policies include preventive and repressive measures. This policy is expected to prevent and reduce the development of beggars both online and offline, as well as encourage the productivity of beggars in society.